An orthopedic manual physical therapy fellowship training's impact on professional development, involvement, personal lives, and income – A survey study. (19th October 2020) - Whitman, Julie M.; Shepherd, Mark; Neilson, Brett; Janicky, T. J.; Garcia, William J.; Peterson, Seth; Stevens, Barbara J.
ABSTRACT: Introduction : Little research exists investigating the personal and professional outcomes of postprofessional physical therapy (PT) training. Therefore, the purpose of the current descriptive, web-based survey study was to determine self-reported outcomes from a postprofessional PT fellowship program, including graduate professional, educational, and research involvement; perceptions of the impact of training on clinical and professional attributes; changes in employment and income; and barriers to training. Methods : Graduates of a part-time, hybrid-model, multisite orthopedic manual PT fellowship program were invited to complete the web-based survey. Descriptive data analyses were performed for all quantitative data, and responses to questions were analyzed and categorized into themes. Results : Of the 77 fellowship graduates, 75 (97%) completed the survey. Graduates were involved in teaching; 43% (32/75) filled lead instructor roles in PT education programs. Further, 75% (57/75) were involved in research. The mean (SD) and median (range) increase in annual gross income was $9560 ($17, 545) and $2, 500 ($0-$125, 000), respectively. Perceived areas with the largest impact of training included clinical reasoning, patient-centered and evidence-based practice, and professionalism. Life balance and family commitments were frequent barriers during training. Discussion : Graduates noted substantial perceived professional, clinical, and financial benefits to fellowship training. Limitations included lack of a control group and surveying participants from a single program. Future research should determine the influence that program and participant-related factors have on personal and professional lives of graduates and on clinical outcomes. Level of Evidence : Descriptive survey, level 3.